Correlation of Walking Activity and Cardiac Hospitalizations in Coronary Patients for 1 Year Post Cardiac Rehabilitation: The More Steps, the Better! - Al Najem, Sinann; Groll, Andreas; Schmermund, Axel; Nowak, Bernd; Voigtländer, Thomas; Kaltenbach, Ulrike; Dohmann, Peter; Andresen, Dietrich; Scharhag, Jürgen (Clinical Medicine Insights: Cardiology, 2022)
Problem: Reducing risk by improving fitness is one of the main objectives of cardiac rehabilitation (CR). To estimate how the number of steps/day post-CR affects coronary patients' prognosis, we analyzed its correlation with the occurrence of death, hospitalizations, and heart complaints, and if and how other variables (ejection fraction (EF), gender, age) relate to those. Methods: One hundred eleven patients (male = 91, female = 20; average age ± standard deviation (SD): 61 ± 11 years) who had been in CR due to recent coronary revascularization or chronic coronary syndrome could be enrolled. Patients were advised to document their steps (daily), blood pressure (daily), weight (weekly) and occurrences of a cardiac event in a diary for 1 year post-CR. A Cox proportional hazard model was used to examine the influence of steps/day, EF, gender, and age until the occurrence of an event. Kaplan-Meier curves were generated to compare patients' profiles. Results: Average steps/day of patients post-CR were 7333 (SD 4426). Increased walking activity reduced risk for cardiac hospitalization (constant steps/day: 5000 vs 7500, hazard rate (HR) reduction of 0.43; 10 000 vs 12 500, HR reduction of 0.20) and risk was higher in patients with an EF < 55% versus EF ⩾ 55% (HR increase of 2.88). Median follow-up time post-CR was 218 days. No patient died, 25 were hospitalized. Discussion: Monitoring the number of steps of coronary patients post CR could be valuable for estimating patients' prognosis.